User Experience Methods and Maturity in Academic Libraries - Young, Scott W. H.; Chao, Zoe; Chandler, Adam (Information Technology and Libraries, 2020)
This article presents a mixed-methods study of the methods and maturity of user experience (UX) practice in academic libraries. The authors apply qualitative content analysis and quantitative statistical analysis to a research dataset derived from a survey of UX practitioners. Results reveal the type and extent of UX methods currently in use by practitioners in academic libraries. Themes extracted from the survey responses also reveal a set of factors that influence the development of UX maturity. Analysis and discussion focus on organizational characteristics that influence UX methods and maturity. The authors conclude by offering a library-focused maturity scale with recommended practices for advancing UX maturity in academic libraries.